BOTTLE MOLD DESIGN IN THE BLOW MOLDING PROCESS USING MASTERCAM X5 AND INVENTOR - tajraihan, nabiel; Santosa, Aa (Jurnal Mekanika dan Manufaktur, 2024)
ABSTRACT In its development, every manufacturing industry increasingly makes humans think more creatively and is faced with new problems, especially in making new innovations. The purpose of these production problems is to achieve faster and more efficient production targets. Manufacturing processes in the plastic field at the present time make products that are in great demand by the public. The development of technology in the dies manufacturing sector due to demands from consumer demand for better quality encourages the Industry to innovate, the process of making dies using metal molds with the aim of improving the quality of the components. Blow Molding is one of the manufacturing processes with the working principle of applying air pressure to plastic material that enters the mold cavity. The mold used is made of metal, either steel or aluminum, to improve the quality of the blow molding process results using a CNC machine where the program created is the result of the Mastercam X5 application. A design process has been carried out to make a mineral water bottle packaging mold using Mastercam X5, to produce Code G which will be used to make molds on a CNC machine, the material used is Aluminium 2024.